Supplemental zinc and vitamin A can alleviate negative effects of heat stress in broiler chickens - Küçük, Ömer; Şahin, Nurhan; Şahin, Kazım (Springernature, 2003)
This experiment was conducted to evaluate the effects of zinc (ZnSO4.H2O) and vitamin A (retinol) supplementation on performance, carcass characteristics, and serum concentrations of glucose, cholesterol, total protein, and malondialdehyde (MDA) as an indicator of lipid peroxidation in broiler chickens (Ross) reared at a high temperature (34 degreesC). One hundred twenty 10-d-old male broilers were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The birds were fed either a basal diet or the basal diet supplemented with either 30 mg Zn/kg diet, 4.5 mg (15,000 IU) retinol/kg diet, or 30 mg Zn + 4.5 mg retinol/kg diet. Supplemental zinc and vitamin A significantly increased live weight gain and improved feed efficiency (p < 0.05). However, a combination of zinc and vitamin A, rather than each separately, provided a greater performance. Hot and chilled carcass weights and yields and the weights of internal organs with the exception of abdominal fat were greater for each supplement (p < 0.05) compared to the control group. Abdominal fat decreased (p < 0.05) upon dietary zinc and vitamin A supplementation. Supplemental treatments resulted in an increased total serum protein but decreased glucose, cholesterol, and MDA concentrations. The results of the study show that, separately or as a combination, zinc and vitamin A supplementation resulted in an improved live weight gain, feed efficiency, and carcass traits, as well as a decrease in serum MDA concentrations. The results of the present study also suggest that zinc and vitamin A have similar effects and that a combination of zinc and vitamin A may offer a potential protective management practice in preventing heat-stress-related depression in performance of broiler chickens.
Keywords: broiler chickens; heat stress; zinc; vitamin A; MDA